Circulating white blood cells affect red cell pulmonary transit times in endurance athletes during intense exercise - Zavorsky, G. S.; van Eeden, S. F.; Walley, K. R.; Russell, J. A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of this study was to determine the relationship between the right-to-left ventricular red cell pulmonary transit times (PTT) during intense exercise and circulating white blood cell (WBC) counts in highly trained endurance athletes. We postulated that high levels of WBCs preexercise would slow PTT. Eleven endurance-trained athletes (VO2max = 69.6 +/- 7.7 mL.kg-1.min-1; weight = 75.0 +/- 6.2 kg; height = 181.0 +/- 7.1 cm) performed 6.5 min constant-load, near-maximal cycling exercise ( approximately 92% VO2max) on two different days. Preexercise WBC counts were measured in arterial blood drawn from the radial artery 30 min before exercise. PTT was measured during the 3rd min of exercise by first-pass radionuclide cardiography using centroid and deconvolution analysis, whereas cardiac output (Q) was measured during the last 2.5 min of exercise via a count-based ratio method from the MUGA technique. RESULTS: Combined mean PTT from both deconvolution and centroid analysis at minute three of exercise was 2.45 +/- 0.21 s, whereas the preexercise WBC count was 5.3 +/- 1.6 x 109.L-1. Cardiopulmonary blood volume at minute three of exercise was 1.22 +/- 0.13 L, VO2 was 4.58 +/- 0.44 L.min-1, and Q was 30.2 +/- 4.2 L.min-1. We found that PTT was negatively correlated with circulating WBC (r = -0.61; adjusted r2 = 0.30; P = 0.04; N = 11) but not with the dispersion (spread) of transit times around the mean (r = 0.19; P = 0.57). CONCLUSION: This suggests that athletes with higher circulating numbers of WBCs preexercise have faster (shorter) red cell transit times through the lung during intense exercise.